Contribution and expression of renal drug transporters in renal cell carcinoma - Zuo, Yawen; Li, Tong; Yang, Shilei; Chen, Xuyang; Tao, Xufeng; Dong, Deshi; Liu, Fang; Zhu, Yanna (Frontiers in Pharmacology, 2025)
Renal cell carcinoma (RCC) is a common substantive tumor. According to incomplete statistics, RCC incidence accounts for approximately 90% of renal malignant tumors, and is the second most prevalent major malignant tumor in the genitourinary system, following bladder cancer. Only 10%–15% of chemotherapy regimens for metastatic renal cell carcinoma (mRCC) are effective, and mRCC has a high mortality. Drug transporters are proteins located on the cell membrane that are responsible for the absorption, distribution, and excretion of drugs. Lots of drug transporters are expressed in the kidneys. Changes in carrier function weaken balance, cause disease, or modify the effectiveness of drug treatment. The changes in expression of these transporters during cancer pathology results in multi-drug resistance to cancer chemotherapy. In the treatment of RCC, the study of drug transporters helps to optimize treatment regimens, improve therapeutic effects, and reduce drug side effects. In this review, we summarize advances in the role of renal drug transporters in the genesis, progression, and treatment of RCC.